Orogenic plateau growth: Expansion of the Turkish‐Iranian Plateau across the Zagros fold‐and‐thrust belt. Issue 2 (26th April 2013) - Allen, M. B.; Saville, C.; Blanc, E. J‐P.; Talebian, M.; Nissen, E.
Abstract: [1] This paper shows how the Turkish‐Iranian Plateau grows laterally by incrementally incorporating adjacent parts of the Zagros fold‐and‐thrust belt. The limit of significant, seismogenic, thrusting in the Zagros ( Mw  > 5) occurs close to the regional 1250 m elevation contour. The seismicity cutoff is not a significant bedrock geology boundary. Elevations increase northward, toward regional plateau elevations of ~2 km, implying that another process produced the extra elevation. Between the seismogenic limit of thrusting and the suture, this process is a plausibly ductile thickening of the basement, suggesting depth‐dependent strain during compression. Similar depth‐dependant crustal strain may explain why the Tibetan plateau has regional elevations ~1500 m greater than the elevation limit of seismogenic thrusting at its margins. We estimate ~68 km shortening across the Zagros Simply Folded Belt in the Fars region, and ~120 km total shortening of the Arabian plate. The Dezful Embayment is a low strain zone in the western Zagros. Deformation is more intense to its northeast, in the Bakhtyari Culmination. The orogenic taper (across strike topographic gradient) across the Dezful Embayment is 0.0004, and across the Bakhtyari Culmination, 0.022. Lateral plateau growth is more pronounced farther east (Fars), where a more uniform structure has a taper of ~0.010 up to elevations of ~1750 m. A >100 km wide region of the Zagros further northeast has a taper of 0.002 and is effectively part of the Turkish‐Iranian Plateau. Internal drainage enhances plateau development but is not a pre‐requisite. Aspects of the seismicity, structure, and geomorphology of the Zagros do not support critical taper models for fold‐and‐thrust belts. Key Points: The Turkish‐Iranian Plateau expands across the Zagros fold‐and‐thrust belt Elevations increase above the limit of seismogenic thrusting Aseismic basement shortening is implicated in this elevation gain